2020
DOI: 10.14245/ns.1938358.179
|View full text |Cite
|
Sign up to set email alerts
|

The Navigated Oblique Lumbar Interbody Fusion: Accuracy Rate, Effect on Surgical Time, and Complications

Abstract: The oblique lumbar interbody fusion (OLIF) can be done with either fluoroscopy or navigation. However, it is unclear how navigation affects the overall flow of the procedure. We wished to report on the accuracy of this technique using navigation and on how navigation affects surgical time and complications. Methods: A retrospective review was undertaken to evaluate patients who underwent OLIF using spinal navigation at University of California San Francisco. Data collected were demographic variables, periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The use of intraoperative stereotactic navigation systems and robotic assistance in OLIF has increased recently [ 20 ], as has the evidence on these technical advancements, which can improve surgical accuracy and patient outcomes. Xi et al [ 93 ] published the results of 214 navigated OLIF cases and reported a cage placement accuracy rate of 94.86%. Only one patient underwent a revisional operation due to cage misplacement, and there was no vascular injury in their series.…”
Section: Recent Advancementsmentioning
confidence: 99%
“…The use of intraoperative stereotactic navigation systems and robotic assistance in OLIF has increased recently [ 20 ], as has the evidence on these technical advancements, which can improve surgical accuracy and patient outcomes. Xi et al [ 93 ] published the results of 214 navigated OLIF cases and reported a cage placement accuracy rate of 94.86%. Only one patient underwent a revisional operation due to cage misplacement, and there was no vascular injury in their series.…”
Section: Recent Advancementsmentioning
confidence: 99%
“…Xi et al demonstrated that use of CaN for the oblique lumbar interbody fusion (OLIF) technique resulted in an accuracy rate of 94.9%, as assessed by postoperative lateral radiographs. 18 Whereas Xi et al evaluated only OLIF, in our study we had 1 misplaced interbody cage requiring intraoperative modification using the LLIF technique, which we attributed to CaN inaccuracy. This single incident suggests that use of CaN for placement of lateral lumbar interbody cages in the adult spinal deformity population is safe and accurate.…”
Section: Discussionmentioning
confidence: 65%
“…The advent and development of navigation technology have had a profound impact on spinal surgery. 22,23 Computer-assisted 3D navigation can provide high-resolution images and a more detailed view of the pedicles, improving the precision of spinal screw placement. As reported in a previous study, the nerve injury risk and clinical complications could be decreased through this technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a less invasive surgery than MIS-TLIF, there are many other percutaneous procedures in Endo-TLIF besides percutaneous screw placement, leading to more radiation exposure. The advent and development of navigation technology have had a profound impact on spinal surgery [ 22 , 23 ]. Computer-assisted 3D navigation can provide high-resolution images and a more detailed view of the pedicles, improving the precision of spinal screw placement.…”
Section: Discussionmentioning
confidence: 99%